Case Report: Infusion-Related Reactions to Intravenous Infliximab and Subcutaneous Ustekinumab in Pediatric Crohn's Disease - Kakiuchi, Toshihiko; Kimura, Sakiko; Esaki, Motohiro; Matsuo, Muneaki (Frontiers in Pediatrics, 2021)
Background: Although the biological agent ustekinumab (UST) is reported to be effective for Crohn's disease (CD) in pediatric as well as adult patients, data on the efficacy and safety of UST in pediatric patients with CD are limited. Here, we describe the case of a pediatric patient who showed an allergic reaction to UST after subcutaneous (SC) maintenance injections but not immediately after initial intravenous (IV) injection. Case Presentation: A 9-year-old boy presented to our hospital with diarrhea lasting 2 years and weight loss, leading to the diagnosis of CD. After prednisolone (PSL) was tapered and discontinued, he promptly relapsed. According to our institution's protocol, we introduced the biological agent infliximab (IFX) with premedication. Coughing and vomiting was observed after the second dose of IFX and it was changed to adalimumab (ADA). However, the effect of ADA gradually disappeared after 18 months; therefore, it was discontinued and he was treated using UST. The first IV UST dose was given after administering hydrocortisone (HDC), an antiallergic and antipyretic analgesic, as premedication, and no obvious adverse reaction was observed. After 8 weeks, UST was subcutaneously injected without premedication. The patient then complained of nausea, dizziness, and headache within 15 min of UST administration. Therefore, for the third dose of UST, HDC was administered again as premedication. However, nausea, dizziness, and headache presented 10 min after UST administration, resulting in discontinuation of further UST treatment. Conclusion: Careful distinction between “true” infusion-related reactions (IRRs) and anaphylaxis or allergic reactions is necessary to determine whether biological agents can be continued after the development of “so-called” IRRs. For true IRRs, it may be possible to continue using the biological agent with appropriate premedication; however, in cases of anaphylaxis, the biological agent itself should be changed.